Constraints in Adoption of Improved Production Technology of Mandarin (Indian Journal of Extension Education, 2014)
The present investigation was carried out in Nagpur district of Maharashtra. Asample of 100 respondents spread over 10 villages of two blocks was selected for the study. The present study revealed that majority of farmers was found to have medium level of adoption of improved production technology of mandarin. The study indicates that farmers had high adoption level of practices viz, the irrigation management, time and spacing for planting, and low adoption practices viz, different varieties of orange, and rejuvenation of old orchards. So there is need to adopt full improved recommended package of practices for increasing the productivity with quality in mandarin orange. The orange growers perceived the constraints like irregular fruit bearing, non availability of disease free improved planting materials, etc.